Psychometric properties of an instrument measuring communication within and between the professional groups licensed practical nurses and registered nurses in anaesthetic clinics - Maria Randmaa; Maria Engström; Gunilla Mårtensson; Christine Leo Swenne; Hans Högberg (BMC, 2019)
Abstract Background The most common cause of clinical incidents and adverse events in relation to surgery is communication error. There is a shortage of studies on communication between registered nurses and licenced practical nurses as well as of instruments to measure their perception of communication within and between the professional groups. The aim of the present study was to evaluate the psychometric properties of the Swedish version of the adapted ICU Nurse-Physician Questionnaire, designed to also measure communication within and between two professional groups: licensed practical nurses and registered nurses. Specifically, the aim was to examine the instrument's construct validity using confirmatory factor analysis and its internal consistency using Cronbach's Alpha. Methods A cross-sectional and correlational design was used. The setting was anaesthetic clinics in two Swedish hospitals. A total of 316 questionnaires were delivered during spring 2011, of which 195 were analysed to evaluate the psychometric properties of the questionnaire. Construct validity was assessed using confirmatory factor analysis and internal consistency using Cronbach's Alpha. To assess items with missing values, we conducted a sensitivity analysis of two sets of data, and to assess the assumption of normally distributed data, we used Bayesian estimation. Results The results support the construct validity and internal consistency of the adapted ICU Nurse-Physician Questionnaire. Model fit indices for the confirmative factor analysis were acceptable, and estimated factor loadings were reasonable. There were no large differences between the estimated factor loadings when comparing the two samples, suggesting that items with missing values did not alter the findings. The estimated factor loadings from Bayesian estimation were very similar to the maximum likelihood results. This indicates that confirmative factor analysis using maximum likelihood produced reliable factor loadings. Regarding internal consistency, alpha values ranged from 0.72 to 0.82. Conclusions The tests of the adapted ICU Nurse-Physician Questionnaire indicate acceptable construct validity and internal consistency, both of which need to be further tested in new settings and samples. Trial registration Current controlled trials http://www.controlled-trials.com Communication and patient safety in anaesthesia and intensive care. Does implementation of SBAR make any differences? Identifier: ISRCTN37251313, retrospectively registered (assigned 08/11/2012).